A History of Derbé Belanbel Historical and Cultural Site - Bogale, Wagaw (Ethiopian Journal of Social Sciences, 2020)
he objective of the study is to reconstruct the history of Derbé Belanbel historical and cultural site. Methodologically the researcher mainly used the qualitative method and culled data from secondary literature but the study heavily relies on field observation and information gathered from knowledgeable informants. As far as I have tried to establish, Derbé Belanbel was a medieval center of culture and civilization of the Harla Somalis characterized by stone built houses, steles, and a Mosque that appropriately suggest a religious settlement. The stone built houses are similar with those located in the Harar, Dire Dawa and Zeila areas as well as with those located in the northern parts of proper Somalia. Though differences in the softness and hardness of the surfaces of the materials used in their productions and the artistic elements we see in them, many of the steles found at Derbé Belanbel display interesting geometric similarity with the Ţiya steles located in the Guraghe Zone of southern Ethiopia. Fragments of pottery, grains of beads, and fragments of glasses that we recovered from the very site suggest the people were skilled in the preparation of household materials from clay soil and had established commercial link as far as the port of Zeila in the northwest and Mogadishu in the east. Overall, though the site is found in a precarious condition owing to lack of attention by the concerned bodies, Derbé Belanbel represented a medieval culture of greater importance, which would immensely contribute to the history of the Ethiopian Somalis and for the growth of the tourism industry of the Regional State. Depending on the effort of the Regional State, the site could be registered in UNESCO as world heritage site.